2006
DOI: 10.1002/hep.21188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the hepatitis B virus genotype and genotype mixtures on the course of liver disease in Vietnam†

Abstract: T he clinical course and long-term outcome of hepatitis B virus (HBV) infection is affected by several factors including viral genotype. For instance, it has been reported that the HBV genotype C induces more severe liver disease than HBV genotype B in Asia, 1,2 whereas HBV genotype A has been more frequently associated with the development of chronic infection than HBV genotype D in Europe. 3 Eight genotypes (A to H) of HBV have been identified based on divergence over the entire genomic sequence of more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
102
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 37 publications
9
102
2
Order By: Relevance
“…Despite the apparent low prevalence of HBV/G throughout the world, the viral genotype appears to circulate globally, as it has been reported in several European countries (De Maddalena et al, 2007;Jardi et al, 2008;Lacombe et al, 2006;Tran et al, 1991;Vieth et al, 2002), North and South America (Alvarado-Esquivel et al, 2006;Bottecchia et al, 2008;Kato et al, 2004;Osiowy & Giles., 2003;Sánchez et al, 2007), Nigeria (Olinger et al, 2006) and Asia (Shibayama et al, 2005;Suwannakarn et al, 2005;Toan et al, 2006). Canadian HBV/G was highly associated with MSM as a risk factor for infection, corresponding to previous studies (Bottecchia et al, 2008;Shibayama et al, 2005;Sánchez et al, 2007).…”
mentioning
confidence: 52%
“…Despite the apparent low prevalence of HBV/G throughout the world, the viral genotype appears to circulate globally, as it has been reported in several European countries (De Maddalena et al, 2007;Jardi et al, 2008;Lacombe et al, 2006;Tran et al, 1991;Vieth et al, 2002), North and South America (Alvarado-Esquivel et al, 2006;Bottecchia et al, 2008;Kato et al, 2004;Osiowy & Giles., 2003;Sánchez et al, 2007), Nigeria (Olinger et al, 2006) and Asia (Shibayama et al, 2005;Suwannakarn et al, 2005;Toan et al, 2006). Canadian HBV/G was highly associated with MSM as a risk factor for infection, corresponding to previous studies (Bottecchia et al, 2008;Shibayama et al, 2005;Sánchez et al, 2007).…”
mentioning
confidence: 52%
“…Among the studies of the HBV genotype in Vietnamese, that of Lindh et al suggested that genotype A was present (17), but Hannoun et al later analyzed those HBV strains in more detail and concluded that it was not certain that genotype A was present (29). To the best of our knowledge, the HBV genotype A in Vietnamese was previously reported in only four patients: three of them were originally from Southern Vietnam (30) and the other was a Vietnamese immigrant in the United States (31); and most recently one study reported that HBV genotypes from A to G were detected in Vietnamese but the prevalence of genotype A was only approximately 18% (32). In contrast to the findings of the above studies in Vietnamese, a study by Song et al reported that genotype A was very commonly observed in HBV-infected Vietnamese patients (98.7%), that the pre-core mutation (G1896A) was not found, and dual core promoter mutations (A1762T/G1764A) were very rare in HCC patients (8%) and were not found in LC patients, CH patients or asymptomatic carriers (ASC) (33).…”
Section: Introductionmentioning
confidence: 92%
“…Genotypes/subgenotypes have distinct geographical distributions: HBV/A and HBV/D are found worldwide, HBV/B and HBV/C are found in east/south-east Asia, HBV/E in west/central Africa, and HBV/F and HBV/H in native populations of the Americas (Araujo et al, 2011; Kramvis et al, 2005). HBV/G was described by Stuyver et al (2000) and, despite low prevalence, seems ubiquitous, as it has been reported in Europe (Lacombe et al, 2006;Vieth et al, 2002), the Americas (Alvarado-Esquivel et al, 2006;Alvarado Mora et al, 2011;Bottecchia et al, 2008;Chu et al, 2003;Osiowy et al, 2008), Asia (Shibayama et al, 2005;Toan et al, 2006) and Africa (Olinger et al, 2006;Toan et al, 2006). HBV/G is frequently reported in patients infected with human immunodeficiency virus (HIV) (Dao et al, 2011;Zehender et al, 2003), particularly in men who have sex with men (MSM) (Bottecchia et al, 2008;Osiowy et al, 2008).…”
mentioning
confidence: 97%